Fair value Accounting between the Advocacy and Opposition - Zahra Hasan Oleiwi; Ibtihaj I Yaqoob (مجلة الغري للعلوم الاقتصادية والادارية)
The conceptual framework of the financial reporting for 2018 clearly indicates fair value as one of the alternatives to the accounting measurement in paragraphs (6-12) and from (12-16) as one of the foundations of the accounting measurement. The increased interest in fair value is due to the unrelenting efforts that coincided with the efforts of (IASB) International Accounting Standard Board and (FASB) Financial Accounting Standard Board through joint action to issue standards, interpretations and clarifications regarding fair value measurement. Through the adoption of (IASB) the standard issued by (FASB) No. (157) in 2006 regarding the fair value as a draft for discussion in 2009, the approaches adopted in the measurement of financial and non-financial assets and liabilities were discussed. These discussions sought to focus on the importance of adopting the fair value because of the information it provides to stakeholders, so that accountants reach a convergence in the issuance of IFRS13 (fair value measurement) in 2011. However, there are conflicting professional and academic attitudes and research trends regarding the adoption of fair value. The article aims to review the two directions of analysis, interpretation and criticism by reviewing some of the studies that are concerned with the topic. The results show that the fair value is an important measurement basis that matches the requirements of stakeholders